Does 'MP3' audio feedback enhance students' learning skills?: An international case study - Issa, Tomayess; Isaias, Pedro; Issa, Theodora (Common Ground Publishing, 2014)
Feedback in higher education, via either traditional or technology approaches, is essential to promote students' skills and knowledge. This study aims to assess students’ responses to the lecturer’s ‘MP3’ audio feedback in four postgraduate units in Australia and Portugal. Two methods are used to provide feedback to the students: traditional and audio ‘MP3’ feedback. The former tracks via a Microsoft word application system, giving academics the chance to include comments regarding what went wrong, and how things might be improved in terms of the topic, structure, layout, style, referencing, grammar and syntax, and proofreading requirements embedded within the assessment. The ‘MP3’ approach, on the other hand, recodes the feedback message using the free software ‘Audacity’. This ‘MP3’ contains a personalized message highlighting the good and bad points, and provides suggestions for improving the final submission. This study provides empirical evidence based on three sources: informal and formal student feedback, and an online survey. The 184 students who participated in the study appeared to be pleased and quite satisfied with the ‘MP3’ audio assessment feedback approach as their learning outcomes and their writing, research, listening, and technology skills were enhanced.